Filtering of plant functional traits is determined by environmental gradients and by past land use in a Mediterranean coastal marsh. (31st December 2014) - Batriu, Efrem; Ninot, Josep Maria; Pino, Joan; Duarte, Leandro
Abstract Question What is the effect of past land use and environmental gradients on plant functional traits within coastal marsh plant communities? Location Mediterranean microtidal marshes in the Llobregat Delta, NE Spain. Methods We used a data set collected previously comprising 45 vegetation plots with associated soil parameters, water table conditions and past land use. For each species we obtained the values or states for a set of plant functional traits: plant height, leaf dry matter content, specific leaf area, seed production, seed weight, life form and lateral expansion. To account for the effect of phylogeny, we evaluated trait diversity skewness by means of an ultrametric phylogenetic tree specifically constructed for the species studied. The association between both environmental gradients and past disturbance, and plant functional traits was tested by means of RLQ analysis. Results Of all the traits, only seed weight showed a phylogenetic signal; consequently, phylogeny was not included in the RLQ analysis. Conductivity was negatively correlated with seed weight, whereas water table conditions and soil ionic balance were negatively correlated with specific leaf area. Past disturbance was negatively correlated with leaf dry matter content and with lateral expansion. Conclusions Plant traits of Llobregat Delta coastal marsh communities are conditioned by environmental gradients and by past land use. Soil ionic balance and water table conditions determine key plant functional traits such as specific leaf area. This finding also corroborates the importance of soil ionic balance as a plant life driver in microtidal Mediterranean marshes. The effect of past land use on species traits might, however, be partially indirect and mediated by associated environmental changes.